Pengaruh Audit Tenure Terhadap Kualitas Audit pada Perusahaan Terbuka di Indonesia - Angela Angela; Marceline Miharja; Wijantini Wijantini; Siti Farhana (Universitas Prasetiya Mulya, 2020)
This paper focuses on analyzing the effect of audit tenure on firm and audit partners on audit quality in non-financial publicly listed companies in Indonesia in the period of 2008 until 2014. The research is motivated by the inconsistent results of previous research in Indonesia and also in other countries. The audit quality is measured by the absolute discretionary accrual proxy using the Modified Jones model (1995). Fundamentally, audit quality describes the results of the performance of independent auditor which is one form of monitoring cost on agency theory. The results show the negative significant relationship between audit firm tenure to audit quality, in line with research from Junaidi et al. (2012), among others. On the other hand, there was no significant relationship between audit partner tenure and audit quality, similar to research from Blandon & Bosch (2017), among others. The result also supported by two types of robustness test. First, using the same model with different period has a negative significant result on audit firm tenure while there was no significant effect on audit partner tenure. Second robustness test using t-test for audit partner tenure on year 1 and 3, and the result shows there is no significant difference in audit quality. The result will be useful as consideration for regulators to concern more to the effect of audit firm tenure compared to tenure partner. keywords: accrual discretionary, audit firm tenure, audit partner tenure, audit tenure, audit quality https://doi.org/10.21632/saki.2.2.224-250